Teaching microeconomics with Islamic perspectives: selected issues and the way forward - Barom, Mohd Nizam; Imon, Riasat Amin; Haneef, Mohamed Aslam (Centre for Islamic Economics, Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia and International Institute of Islamic Thought, 2024)
This final chapter serves as the concluding chapter for this book. It highlights several major observations from the experience of the selected Southeast Asian universities in teaching microeconomics with Islamic perspectives, and the main issues faced by these institutions. The chapter offers several proposals in dealing with these issues. Finally, recognising the enormous tasks ahead for the development of Islamic economics education, the chapter ends by highlighting the need for better collaboration among the various institutions towards continuous improvement of the quality of Islamic economics education. This can be facilitated by the role that the International Federation of Islamic Economics and Finance Education (I-FIEFE) can play in the region.